Npas4 regulates medium spiny neuron physiology and gates cocaine‐induced hyperlocomotion. (18th October 2021) - Lissek, Thomas; Andrianarivelo, Andry; Saint‐Jour, Estefani; Allichon, Marie‐Charlotte; Bauersachs, Hanke Gwendolyn; Nassar, Merie; Piette, Charlotte; Pruunsild, Priit; Tan, Yan‐Wei; Forget, Benoit; Heck, Nicolas; Caboche, Jocelyne; et al.
Abstract: We show here that the transcription factor Npas4 is an important regulator of medium spiny neuron spine density and electrophysiological parameters and that it determines the magnitude of cocaine‐induced hyperlocomotion in mice. Npas4 is induced by synaptic stimuli that cause calcium influx, but not dopaminergic or PKA‐stimulating input, in mouse medium spiny neurons and human iPSC‐derived forebrain organoids. This induction is independent of ubiquitous kinase pathways such as PKA and MAPK cascades, and instead depends on calcineurin and nuclear calcium signalling. Npas4 controls a large regulon containing transcripts for synaptic molecules, such as NMDA receptors and VDCC subunits, and determines in vivo MSN spine density, firing rate, I/O gain function and paired‐pulse facilitation. These functions at the molecular and cellular levels control the locomotor response to drugs of abuse, as Npas4 knockdown in the nucleus accumbens decreases hyperlocomotion in response to cocaine in male mice while leaving basal locomotor behaviour unchanged. SYNOPSIS: The activity‐controlled transcription factor Npas4 is induced in striatal medium spiny neurons (MSNs) through a different signaling pathway than other IEGs and controls key MSN cellular parameters, as well as the magnitude of cocaine‐induced hyperlocomotion. Npas4 induction in MSNs is regulated by NMDA receptors (NMDARs), voltage‐dependent calcium channels (VDCCs), calcineurin, CaMKII/IV and nuclear calcium signaling, and is independent of D1 dopamine receptor, protein kinase A or MAPK activity. Npas4 regulates the transcription of NMDAR subunit genes Grin1, Grin2a and Grin2b, as well as VDCC subunit genes Cacna1c and Cacna1d in MSNs. Npas4 controls spine density in D1‐MSNs, but not in D2‐MSNs, and determines MSN electrophysiological properties in vivo . Npas4 regulates the strength of cocaine‐induced hyperlocomotion over the course of sensitization. Abstract : The activity‐controlled transcription factor Npas4 is induced in striatal medium spiny neurons (MSNs) through a different signaling pathway than other IEGs and controls key MSN cellular parameters, as well as the magnitude of cocaine‐induced hyperlocomotion.